2016
DOI: 10.1097/gme.0000000000000689
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular, hemodynamic, neuroendocrine, and inflammatory markers in women with and without vasomotor symptoms

Abstract: Objective Vasomotor symptoms (VMS) may be associated with an increased risk of cardiovascular disease. One candidate mechanism may involve alterations in physiological responses to stress. The current study therefore examined the relationship between self-reported VMS bother and cardiovascular, hemodynamic, neuroendocrine and inflammatory responses to an acute psychosocial stress protocol. Methods One hundred and eighty-six women in the menopause transition or early postmenopause (age 45-60) provided the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 55 publications
(58 reference statements)
2
19
1
4
Order By: Relevance
“…34 The disturbances in the ANS and HPA axis may serve as a common link between VMS and CVD. 35,36 Hot flashes and night sweats may lead to different physiological changes in women. In one study, women with daytime hot flashes were reported to be leaner and had lower systolic blood pressure than women with night sweats.…”
Section: Mechanismsmentioning
confidence: 99%
“…34 The disturbances in the ANS and HPA axis may serve as a common link between VMS and CVD. 35,36 Hot flashes and night sweats may lead to different physiological changes in women. In one study, women with daytime hot flashes were reported to be leaner and had lower systolic blood pressure than women with night sweats.…”
Section: Mechanismsmentioning
confidence: 99%
“…However, because we found an association between hot flashes and MetS, future studies could consider the occurrence of hot flashes as a risk marker for CVD and MetS. In fact, there have been numerous studies showing that hot flashes are associated with activation of the hypothalamic-pituitary-adrenal axis, with the release of cortisol, and with norepinephrine stimulation 24,25 . Therefore, the only way to establish causality among these factors in a more consistent manner is to conduct longitudinal cohort studies.…”
Section: Discussionmentioning
confidence: 72%
“…In the group of premenopausal patients with VMS, there was a positive correlation between the PLR and baseline arterial diameter, which indicates that women with hot flashes have greater inflammation that affects the vascular endothelium [ 9 , 40 - 42 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%